Optimization of Preparation Process and Antioxidant Activity of Kidney Bean-Haskap Composite Fermentation Liquid - Jia WANG; Fangli DING; Yu AN; Xueying ZENG; Zhihui ZHANG; Sinan LI; Kaiyuan XU; Fang ZHOU; Ying WANG; Lu ZHANG; Bingzheng XU; Zekun SUN (Shipin gongye ke-ji)
In order to improve the utilization value of grains and small berries, the fermentation liquid of kidney bean and haskap was prepared by compound lactic acid bacteria and the fermentation parameters were optimized. Specifically, four kinds of lactic acid bacteria were selected to inoculate and ferment the composition liquid of kidney bean and haskap. After screening the compound lactic acid bacteria based on the number of live bacterial count as the index, the process parameters of the composite fermentation liquid were determined using single factor test and response surface optimization test, as well as its physical and chemical properties, biological activity and antioxidant capacity were evaluated. The compound lactic acid bacteria L1:L2 was selected and inoculated in the composition liquid of kidney bean and haskap. The optimal process parameters of the composite fermentation liquid were a compounding ratio of 1:1, an initial pH of 5.0, an inoculation amount of 2%, and a fermentation temperature at 34 ℃. Under these conditions, the live bacterial count in the composite fermentation liquid was 9.89 lg CFU/mL. The maximum values of total phenol and flavonoid reached at 16 h during fermentation, which were 2204.96 µg/mL and 701.09 µg/mL, respectively. The antioxidant experiments showed that the DPPH and ABTS+ free radical scavenging rates of composite fermentation liquid initially increased and then decreased slowly, with the highest scavenging values of 98.23% and 93.77%, respectively. The optimal process parameters resulted in a strong antioxidant capacity in the composite fermentation liquid of kidney bean and haskap.